Lamellar network structure constructed by ZnSe/C nanorods for high-performance potassium storage. (1st July 2022) - Wang, Lili; Zhang, Anbang; Li, Na; Yuen, Anthony Chun Yin; Deng, Chonghai; Dong, Qiang; Zhang, Lingyun; Yeoh, Guan Heng; Yang, Wei
Highlights: Novel ZnSe/C lamellar network structure was synthesized via a facile method. LN-ZnSe/C showed excellent electrochemical performance for K-ion batteries. The enhanced performance was attributed to the 3D ion/electron traffic networks. Abstract: The rapid development of promising potassium-ion batteries (PIBs) is still greatly hindered by typical constraints, including sluggish diffusion kinetics and structural degradation caused by severe volume vibration during the intercalation/deintercalation of K + . To eliminate such issues, herein we designed a novel lamellar network structure constructed by carbon-coated ZnSe/C nanorods (LN-ZnSe/C) as the anode of PIBs. The LN-ZnSe/C composite was synthesized via glucose-assisted freeze-drying and subsequent in-situ selenization of the zinc tartrate precursor. Kinetics analysis revealed that the nanosize and lamellar network structure of ZnSe/C enabled fast K-ion diffusion. Meanwhile, the carbon layer, as the binder and structure reinforcer of the ZnSe nanorods, provided a stable interconnected conductive network and enhanced the mechanical integrity of ZnSe for volume variation. Benefitting from these merits, LN-ZnSe/C revealed high reversible capacity (383 mA h g −1 at a current density of 200 mA g −1 after 100 cycles), superior rate capacity (230 mA h g −1 at 5 A g −1 ), and long cycling life (179 mA h g −1 after 1200 cycles at 1 A g −1 ). This work demonstrates a new promising development framework for fabricating network structures with a 3D charge-transport system to advance potassium-based energy storage devices. Graphical abstract: Image, graphical abstract